2005
DOI: 10.1016/j.envpol.2005.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of arsenate on soils. Part 2: Modeling the relationship between adsorption capacity and soil physiochemical properties using 16 Chinese soils

Abstract: Citrate-dithionite extractable Fe has the most important positive influence on arsenate adsorption on soils. AbstractAn attempt has been made to elucidate the effects of soil properties on arsenate adsorption by modeling the relationships between adsorption capacity and the properties of 16 Chinese soils. The model produced was validated against three Australian and three American soils. The results showed that nearly 93.8% of the variability in arsenate adsorption on the low-energy surface could be described … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
43
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 19 publications
8
43
0
Order By: Relevance
“…The equation showed significant correlation with R values ranging from 0.996 to 0.998 (p < 0.01). The As(V) sorption generally increased with increasing initial As(V) concentrations from 0 to 2.0 mM, and the soil showed a rather higher sorption capacity for As(V) compared with the reported data for As(V) sorption on soils (Livesey and Huang, 1981;Jiang et al, 2005). The XRD analysis indicated only minor amounts of iron oxides in the soil.…”
Section: Arsenate Sorption In the Red Soilmentioning
confidence: 74%
See 3 more Smart Citations
“…The equation showed significant correlation with R values ranging from 0.996 to 0.998 (p < 0.01). The As(V) sorption generally increased with increasing initial As(V) concentrations from 0 to 2.0 mM, and the soil showed a rather higher sorption capacity for As(V) compared with the reported data for As(V) sorption on soils (Livesey and Huang, 1981;Jiang et al, 2005). The XRD analysis indicated only minor amounts of iron oxides in the soil.…”
Section: Arsenate Sorption In the Red Soilmentioning
confidence: 74%
“…However, the ratios of oxalate to citrate-dithionate extractable Al and Fe (0.30 for Al and 0.14 for Fe) suggested that significant proportions of Al and Fe were in forms of low crystallinity (Johnson et al, 1986). This accounted for the high sorption capacity of the soil (Livesey and Huang, 1981;Jiang et al, 2005). With the increasing As(V) sorption, significant enhancements in the release of dissolved organic carbon (DOC) and the major inorganic anions, such as OH − and PO 4 3− , were observed (Table 3).…”
Section: Arsenate Sorption In the Red Soilmentioning
confidence: 99%
See 2 more Smart Citations
“…The As (V) adsorption on ACpa occurred predominantly on the low-energy surface. Soil properties strongly affect As adsorption and subsequently influence the environmental fate of As (Jiang et al 2005b, Buschmann et al 2006, Girouard and Zagury 2009. Jiang et al (2005a) suggested that the Langmuir two-surface equation describes As (V) adsorption better than the Langmuir one-surface equation for soils with lower contents of OM, DOC, or extractable P, where both high-energy and low-energy surface adsorption sites would be available.…”
Section: Resultsmentioning
confidence: 99%